Decarboxylative/decarbonylative C3-acylation of indoles via photocatalysis: a simple and efficient route to 3-acylindoles. Issue 18 (6th June 2016) - Shi, Qing; Li, Pinhua; Zhu, Xianjin; Wang, Lei
Abstract : An efficient synthesis of 3-acylindoles via visible-light promoted C3-acylation of free (NH)- and N -substituted indoles with α-oxocarboxylic acids was developed. Abstract : A simple and efficient strategy for the preparation of 3-acylindoles via visible-light promoted C3-acylation of free (NH)- and N -substituted indoles with α-oxocarboxylic acids was developed. The reaction tolerates a wide range of functional groups, and the corresponding 3-acylindoles were obtained in high yields under mild conditions.